Cross sectional, qualitative thematic analysis of patient perspectives of disease impact in juvenile idiopathic arthritis-associated uveitis - Ethan S. Sen; Michelle J. Morgan; Rachael MacLeod; Helen Strike; Ann Hinchcliffe; Andrew D. Dick; Brinda Muthusamy; Athimalaipet V. Ramanan (BMC, 2017)
Abstract Background Chronic health conditions in children can have a significant impact on their quality of life. The aim of this study was to explore the subjective experience of children and young people being treated for chronic, non-infectious uveitis associated with a systemic disease such as juvenile idiopathic arthritis. Methods A semi-structured interview was conducted with 10 children and young people aged between 6 and 18 years of age and their parents. Results Preliminary thematic analysis indicated that both the treatment and complications of the disorder have a significant impact on the quality of life and emotional well-being of patients, not only in terms of the discomfort experienced but also in perceptions of social isolation, anxiety and sense of injustice. Conclusion This study shows that themes including "impact on school", "social factors" and "emotional reactions" are important domains influencing health-related quality of life (HRQoL) in children with chronic uveitis. Inclusion of questions relating to these domains should be considered in future uveitis-specific tools examining HRQoL in these patients.